B Cells and Antibodies in Transplantation. Issue 7 (July 2016) - Koenig, Alice; Mariat, Christophe; Mousson, Christiane; Wood, Kathryn J.; Rifle, Gérard; Thaunat, Olivier
Abstract : Abstract: Overlooked for decades, the humoral alloimmune response is increasingly recognized as a leading cause of graft loss after transplantation. However, improvement in the diagnosis of antibody-mediated rejection has not yet translated into better outcomes for transplanted patients. After an update on B cell physiology and antibody generation, the 2015 Beaune Seminar in Transplant Research challenged the conventional view of antibody-mediated rejection pathophysiology and discussed the latest promising therapeutic approaches. Abstract : A summary of the 2015 Beaune Seminars in Transplant Research discussing issues related to B cell physiology and antibody generation, current state in diagnosing pathogenic DSA and antibody-mediated rejection, and new treatment strategies.